A new species of Discochiton Hodgson & Williams (Hemiptera: Coccomorpha: Coccidae) on bamboo from Myanmar - Choi, Jinyeong; Lee, Seunghwan (Zootaxa, 2023)
The adult female and first-instar nymph of a new species of Discochiton Hodgson & Williams, 2018, Discochiton bambusae Choi & Lee sp. n. are described and illustrated. They were collected on the culms of Bambusa tulda (Poaceae: Bambusoideae) in Myanmar. The adult female has several unique morphological features, such as a large body, up to 15 mm long; legs much reduced; and sclerotized plates forming submedial bands or patches on the venter. Furthermore, the adult female has more marginal radial lines and stigmatic spines than are found in other Discochiton species. The first-instar nymph is also much larger than those of other Discochiton species, and is also distinct in having tibial setae, and a greater number of spiracular disc-pores and marginal setae compared to those of other species of Discochiton.